α-Imino gold carbenes from 1,2,4-oxadiazoles: atom-economical access to fully substituted 4-aminoimidazoles - Zeng, Zhongyi; Jin, Hongming; Xie, Jin; Tian, Bing; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Organic letters, 2017)
A novel and atom-economical synthesis of fully substituted 4-aminoimidazoles via gold-catalyzed selective [3 + 2] annulation of 1,2,4-oxadiazoles with ynamides is reported. This protocol represents a new strategy to access α-imino gold carbenes, which corresponds to an unprecedented intermolecular transfer of N-acylimino nitrenes to ynamides. Moreover, the reaction proceeds with 100% atom economy, exhibits good functional group tolerance, and can be conducted in gram scale.
Gesehen am 28.08.2017